Mediações da imagem na educação a distância - Lins, Andreia Chiari (2008)
This doctoral research, realized at the Program of Post-Graduated on Educacion - Universidade Federal do Espírito Santo (UFES) -, analyzes the production of didactic images in the course Visual Arts – Distance Education (EAD), from the categories of mediation and contradiction. Investigates: Which mediating categories emerge in the field of courseware production, in a distance learning mode? How these particular contexts affect the imaging process in the teaching material? The theoretical framework of the research focuses on the historical and dialectical materialism, particularly the concepts of mediation and contradiction based on Marx and Engels (1985, 1996, 1998, 2001, 2008), Mészáros (2006), Konder (1998) Smolka and Nogueira (2002), Lukacs (1979), Vigotski (2003), Ciavatta (2004). It aims to know the mediations and contradictions inherent in the teaching image production process, analyzing limits and materials production possibilities in the course of Arts-EAD. The research performs data collection in the context of image production for the course Arts-EAD, in its 2nd offer, in the disciplines of the first module. Takes the view that the didactic image has its own mediating categories and its changes while the educational material production process, especially in teaching mediation. This allows studies of productive context. Data were produced during a year of observation, document analysis, interviews, discussions and monitoring the production of educational materials in six subjects of the course Arts-EAD. Qualitative research base was supplemented with quantitative data. In the five analyzes the situations encountered explicit mediations and contradictions inherent in the process. The analysis of the context studied show process of contradictions, in which these subjects are intertwined in terms of the structures given to teaching and learning. These analytics show mediations given that particular process. It is evident as the given conditions, the individuals and collective decisions promote changes in the production of "didactic pictures", assessing them results and modes of educational uses that were not conceived initially, increasing the teaching process or generating contradictions. Three analytical studies have been done from the necessity of the degree in Visual Arts - EAD use images of works of art as a didactic image. The research and analysis showed how the work of art and the image became goods regulated by their owners and by national legislation in its diversity of forms and 10 demonstrated how the procedural actions of the subject producers change between the initial pedagogical proposal devised by the teacher and the result of the product generated. Within the same analytical proposal, two other studies on the didactic images were made from images produced in UFES animation techniques and illustration. So in five cases sought to demonstrate how and which mediating categories of analysis on the production process transformed the initial pedagogical proposal. The research results allow us to understand which factors increase the difficulty to access the production of pictorial materials for general education. Research indicates the need for changes in the modes of producing imagery teaching materials and training of teachers of distance education